Accuracy of Transcranial Ultrasound in the Detection of Mild White Matter Lesions in Newborns. Issue 3 (1st June 2013) - Ciambra, G.; Arachi, S.; Protano, C.; Cellitti, R.; Caoci, S.; Di Biasi, C.; Gualdi, G.; De Curtis, M.
Cranial Ultrasound (cUS) may not be sensitive enough to detect subtle white matter (WM) injuries. Our study compared serial cUS with MRI at term equivalent age (TEA) to determine if it is possible to identify an ultrasound representation of subtle diffuse WM injuries such as punctate lesions (PWMLs) and diffuse excessive high signal intensity (DEHSI). Fifty-six very preterm infants were scanned sequentially from birth to TEA, an MRI was performed at TEA. Each echodensity found on cUS was classified as absent, transient (≤7 days), or prolonged (>7 days). A transient periventricular echodensity was detected in seven infants (12.5%), and a prolonged echodensity in 15 (26.8%). MRI examinations were performed in all 56 infants. No altered signal intensity was found in 18 infants (32.1%). DEHSI was detected in 14 infants (25%), and PWMLs were detected in eight babies (14.3%). Both abnormalities were found in 16 infants (28.6%). The positive predictive values of the prolonged echodensity for DEHSI and PWMLs were 86.7% and 46.7% respectively. However, a significant statistical correspondence (p=0.002, Odds Ratio 11.9) was found comparing DEHSI with cUS abnormal echodensities. Serial cUS during the neonatal period in preterm infants is essential and cannot be replaced with MRI at TEA. MRI seems to be more reliable in detecting mild or moderate WM abnormalities. However, serial cUS performed by an experienced neonatologist can provide valuable information on early WM changes such as prolonged echodensities that could potentially lead to a diffuse injury.